2018
DOI: 10.1021/acs.cgd.7b00709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Self-Assembly Behavior of Fmoc-Phenylalanine and Corresponding Peptoid Derivatives

Abstract: Fluorenylmethoxycarbonyl-protected phenylalanine (Fmoc-Phe) derivatives are a privileged class of low molecular weight amino acid hydrogelators that undergo spontaneous selfassembly in water to form one-dimensional (1D) fibril networks. Structural studies indicate that these fibrils feature unidirectional hydrogen bonding and parallel π−π interactions (Fmoc−Fmoc and side chain benzyl−benzyl), which stabilize the 1D fibrils. However, the relative contribution of hydrogen bonding vs π−π interactions in these ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…The gel showed enhanced dye diffusion and faster gel erosion at higher temperature suggesting further exploration of the molecule in drug delivery (Singh et al, 2015). The unidirectional hydrogen bonding of the carbamate group within Fmoc-Phe-OH assemblies directed the assembly into 1D fibrils while Fmoc-peptoid analogs displayed 2D/3D morphology due to the alteration in H-bonding (Rajbhandary et al, 2018).…”
Section: Single or Modified Single Amino Acidsmentioning
confidence: 98%
“…The gel showed enhanced dye diffusion and faster gel erosion at higher temperature suggesting further exploration of the molecule in drug delivery (Singh et al, 2015). The unidirectional hydrogen bonding of the carbamate group within Fmoc-Phe-OH assemblies directed the assembly into 1D fibrils while Fmoc-peptoid analogs displayed 2D/3D morphology due to the alteration in H-bonding (Rajbhandary et al, 2018).…”
Section: Single or Modified Single Amino Acidsmentioning
confidence: 98%
“…There is an argument that there is a link between the gel and crystal phase or at least there is sufficient structural similarity to infer packing in the gel from a crystal structure. [14][15][16][17][18][19][20][21][22] Important motifs that lead to specific types of one-dimensional interaction in certain crystal structures have been used to guide design of further analogues. It is not uncommon with this approach to grow crystals in one solvent mixture and infer information as to packing to design gelators for a completely different solvent system.…”
Section: Introductionmentioning
confidence: 99%
“…Others have also shown that crystals can be grown from the gel phase in a range of systems. 14,[36][37][38][39][40][41][42][43][44] This can be spontaneous. 45 For example, Andrews et al have shown a case where a metastable gel transforms to a crystal phase, leading them to suggest that for their case the gelation is the first stage of the crystallisation process.…”
Section: Introductionmentioning
confidence: 99%
“…Once a high enough concentration of these vesicles accumulates, they are thought to fuse into tubes. 7,11,18 Finally, the nanotube comes together in a more piece-wise cooperative manner. It suggests that the side chains of adjacent FF dipeptides “zipper” together to form ringlike structures while stacking up into a tube.…”
Section: Introductionmentioning
confidence: 99%
“…11 Additionally, more extensive hydrogen bonding was found to allow for high-aspect-ratio packing, further stabilizing the nanotubes. 11 A similar study of phenylalanine–alanine nanotubes confirmed the presence of both (NH)H···O carbonyl hydrogen bonding. 16…”
Section: Introductionmentioning
confidence: 99%